(untitled) (The Journal of Plant Protection Sciences, 2022)
A field investigation was conducted to evaluate the efficacy of some insecticides against soil pests i.e. cutworm (Agrotis ipsilon Hufner; Noctuidae: Lepidoptera) and molecricket (Gryllotalpa africana P. de Beau; Gryllotalpidae: Orthoptera) infesting potato at Adisaptagram Block Seed Farm, Mogra, Hooghly, West Bengal (India) during 2007-08 and 2008-09. The field trial was conducted in Randomized Blocked Design with six treatments and five replications. Among the various treatments for managing soil pests of potato (cv. Kufri Bahar) i.e. cutworm and molecricket soil treatment of -1 phorate 10 G @ 15kg ha at planting plus drenching the ridges with chlorpyriphos 20 EC @ 2.5ml/L of water on appearance of pest (T ) was found most effective in decreasing the incidence of cutworm and molecricket followed by soil 5-1 treatment at planting with phorate 10 G @ 15kg ha with addition drenching the ridges with imidacloprid 17.8 SL @ 0.004% (2ml/10 L of water) on the occurrence of the pest (T ) than other treatments as well as control. Both the treatments 6 (T and T ) were more or less equally effective to decrease the incidence of cutworm and molecricket. Yield of healthy 5 6-1 tubers was recorded maximum (31.66 t ha ) in T treatment succeeds by T than other treatments as well as control. 5 6